Le fonctionnement ambivalent de la propriété intellectuelle dans « l’économie créative » - Vincent Bullich (Communication)
Spokespersons for the “creative industries” have long stressed the importance of a legal framework with strong intellectual property protection to ensure growth. In the first part of the article the author succinctly describes the background against which the concept of “creative industries” emerged and identifies specific characteristics of their products. He goes on to advance a theory on the contribution of intellectual property rights to the singularization process that increasingly characterizes the “creative” goods and services economy. In the third part he assesses the scope of this process in terms of the ways such products are valued.